2001
DOI: 10.1177/1358836x0100600106
|View full text |Cite
|
Sign up to set email alerts
|

Altered gait profile in subjects with peripheral arterial disease

Abstract: Abstract:The purpose of this study was to determine whether peripheral arterial disease (PAD) subjects had impaired temporal and spatial gait characteristics compared to non-PAD controls at preferred and rapid self-selected walking paces. A total of 28 PAD subjects with intermittent claudication (age = 71 ± 1; mean ± SEM) and 15 non-PAD controls with at least one cardiovascular risk factor but no ambulatory leg pain (age = 71 ± 1) were recruited. Gait parameters consisting of velocity, cadence, stride length, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 22 publications
7
63
1
5
Order By: Relevance
“…Como foi demonstrado que pacientes com DAOP e CI apresentam alterações na marcha, mesmo na ausência de dor (10,11,12) , Crowther et al (10) sugeriram que pesquisas futuras avaliassem os efeitos de pro-logo após a manifestação de uma disfunção, a velocidade de caminhada foi mais lenta por não haver aumento proporcional na cadência. De acordo com Scherer et al (11) , a isquemia de um músculo ou grupo muscular pode ser um fator primário na determinação das caracterís-ticas de marcha apresentadas por essa população.…”
Section: Discussionunclassified
See 3 more Smart Citations
“…Como foi demonstrado que pacientes com DAOP e CI apresentam alterações na marcha, mesmo na ausência de dor (10,11,12) , Crowther et al (10) sugeriram que pesquisas futuras avaliassem os efeitos de pro-logo após a manifestação de uma disfunção, a velocidade de caminhada foi mais lenta por não haver aumento proporcional na cadência. De acordo com Scherer et al (11) , a isquemia de um músculo ou grupo muscular pode ser um fator primário na determinação das caracterís-ticas de marcha apresentadas por essa população.…”
Section: Discussionunclassified
“…gramas de reabilitação, realizados por meio do exercício físico supervisionado, sobre os parâmetros espaço-temporais e cinemáticos da marcha, com intuito de providenciar maior compreensão a respeito da interferência da DAOP e CI durante o ato de caminhar. Já Gardner et al (12) especularam que, por meio do exercício físico, alterações nos parâmetros da marcha pudessem ocorrer, ocasionando, portanto, menor gasto energético durante o caminhar e melhora da CI. Porém, no presente estudo verificou-se que a velocidade de marcha, a cadência e o comprimento da passada, na ausência de dor, foram similares entre os participantes de programas de reabilitação em curto e em longo prazos, logo após seus términos.…”
Section: Marchaunclassified
See 2 more Smart Citations
“…Patients with symptomatic PAD are at particularly high risk for slow gait due to the development of leg pain during ambulation, thereby placing them at even higher risk for morbidity and mortality. In fact, we have found that gait speed is slower in PAD patients than in controls even during pain-free ambulation (Gardner et al 2001). One possible mechanism for slow gait speed in older patients with PAD is their chronically high levels of inflammation and oxidative stress, which leads to muscle breakdown and sarcopenia (Clegg et al 2013).…”
Section: Introductionmentioning
confidence: 89%